Typical Properties of Beverages with Different Ethanol Content: A Comparative Analysis - Igor P. Lutkov; Dmitry V. Yermolin (Техника и технология пищевых производств)
Non-alcoholic beer and wine are in great demand. Some of them contain carbon dioxide. Dealcoholization makes it possible to obtain high-quality drinks, but changes in flavor and taste are unavoidable. This article introduces a comparative analysis of the typical properties of beer and sparkling wine with different levels of alcohol. The research featured industrial samples of beer and sparkling wine with different volume fractions of ethyl alcohol. The comparative analysis relied on standard research methods and included sensory evaluation, acidity, sparkling properties in terms of carbon dioxide desorption rate, carbon dioxide content, foamy properties, viscosity, phenolic substances, beer proteins, and optical characteristics. Alcoholic beer had a better taste and possessed a typical beer flavor. The flavor and taste profile of sparkling wines depended on the raw material. The sparkling coefficient of non-alcoholic beer was 1.2–7.5% higher than that of alcoholic beer because drinks with less ethanol have better carbon dioxide solubility. For alcoholic sparkling wine, the sparkling coefficient was higher by 19.7% than for its non-alcoholic analogue due to bound forms of carbon dioxide. The foaming properties of alcoholic drinks were better than those of the non-alcoholic samples due to the higher protein content. The yellowness and optical density of drinks at a wavelength of 350 nm depended on the amount of phenolic substances. The color index of beer depended on the content of melanoidins. The modern dealcoholization technologies make it possible to produce non-alcoholic beverages with the same sensory properties as their alcoholic prototypes. However, these technologies can be improved in terms of bound carbon dioxide, proteins, phenolic substances, and flavor.